ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN YANG MELAKUKAN AKUISISI - Hindryanto, Stefany; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to test whether there are some differences between financial performances in thecompany which has carried out the acquisition. The financial performance has been measured by usingfinancial ratio i.e. liquidity ratio, activity ratio, solvability ratio and profitability ratio. The population is allcompanies which have carried out the acquisition in 2011-2013 periods are listed in Indonesia Stock Exchange.The sample collection technique has been conducted by using purposive sampling technique and 11 companieswith the research period during 2 years before and after the acquisition have been obtained as samples. Thehypothesis test has been carried out by using non-parametric test i.e. Wilcoxon Signed Rank Test. Based on theresult of the research, it has been found that there are some differences between activity and profitability ratiobefore and after the acquisition. Meanwhile, liquidity and solvability ratio does not have any difference beforeand after the acquisition. It is caused by the synergy which has been obtained from the acquisition activitycannot be seen in the short term period, because a long period of time is required in order to increase thefinancial ratio of the company.Keyword: Acquisition, financial performance, financial ratio